Foreign Office and Foreign and Commonwealth Office: Embassy and Consulates, Egypt: General Correspondence (F.O. 141) (Records of the Public Record Office., 1970)
This series contains general correspondence of the British embassy and consulates in Egypt and the United Arab Republic.